Risk perceptions, health, and policy support in China: an analysis of WeChat group posts during the COVID-19 pandemic in 2022 - Xiao Wang (Discover Public Health)
Abstract Aim This investigation aimed to reveal Chinese attitudes toward COVID-19 and support for the zero-COVID policy during the Shanghai lockdown and December policy easing in 2022. Method It adopted primarily a textual analysis of four WeChat groups, including a residential group in Shanghai and two alum and class groups with members in mainland China, Hong Kong, Macao, and overseas. Results The results revealed that group members generally perceived greater severity, especially when COVID-19 infection risks were spatially or temporally close than distant or if they were more collectivist than individualistic. However, lived experiences of COVID-19 infections recalibrated the members’ risk perceptions: Those initially fearful became less fearful; those initially dismissive of COVID-19 risks later understood the real and differential impacts on the population. The results also showed that the residential and alum groups generally supported zero-COVID before November 2022 and did not discuss zero-COVID afterward. The class group showed nuanced results that were strongly dependent on group dynamics and members’ personalities. Conclusion This article showcases how a textual analysis of social media groups can reveal a detailed understanding and progression of Chinese risk perceptions in 2022 and how psychological distance, values, and lived experiences advance risk communication theory.